Plasma flow chemistry for direct N-acylation of amines by esters. Issue 52 (9th June 2022) - Abedelnour, Elias; Ognier, Stephanie; Zhang, Mengxue; Schio, Laurent; Venier, Olivier; Cossy, Janine; Tatoulian, Michael
Abstract : The synthesis of N -acylamines by using a plasma gas/liquid flow microreactor without any additives is reported, N -acylamines were obtained in good to excellent yields from primary and secondary amines, as well as from anilines, using different esters. Abstract : The direct N -acylation of amines by esters in a microreactor is described using argon plasma, thereby producing amides in good to excellent yields.